2002
DOI: 10.1046/j.1365-8711.2002.05707.x
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared spectroscopy of protoplanetary and planetary nebulae

Abstract: We present medium-resolution (R ∼ 600), mid-infrared (7.5-14 µm) spectra of 15 young planetary nebulae. Linestrengths for observed forbidden transitions are presented, and numerous broad emission features from silicates, polyaromatic hydrocarbons (PAHs) and silicon carbide (SiC) are observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
(26 reference statements)
1
7
0
Order By: Relevance
“…The SWS spectrum of M 4‐18 is very noisy, although the PAH features are unquestionably detected. However, the spectral levels of the PAH bands in this SWS spectrum match those in the spectrum by Rinehart et al (2002) to within 10 per cent, confirming our estimate of I (7.7)/ I (IR) for this object. In the small sample of PNe studied by Cohen et al (1989), NGC 6302 substantively helped to define the trend at 7.7 μm because of its low C/O ratio.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The SWS spectrum of M 4‐18 is very noisy, although the PAH features are unquestionably detected. However, the spectral levels of the PAH bands in this SWS spectrum match those in the spectrum by Rinehart et al (2002) to within 10 per cent, confirming our estimate of I (7.7)/ I (IR) for this object. In the small sample of PNe studied by Cohen et al (1989), NGC 6302 substantively helped to define the trend at 7.7 μm because of its low C/O ratio.…”
Section: Resultssupporting
confidence: 84%
“…M 4‐18 has the largest value of I (7.7)/ I (IR). Ground‐based spectra (Aitken & Roche 1982; Rinehart et al 2002) clearly show its 11.3‐μm band although its 8.7‐μm feature is convincingly shown only by the Aitken & Roche (1982) spectrum from Mauna Kea. The SWS spectrum of M 4‐18 is very noisy, although the PAH features are unquestionably detected.…”
Section: Resultsmentioning
confidence: 99%
“…Recent Spitzer observations show that planetary nebulae (PNe) in the LMC often show strong SiC emission (Stanghellini et al 2007;Bernard-Salas et al 2008), while in Galactic PNe, it is generally weak (Barlow 1983;Rinehart et al 2002). The presence of SiC features in EROs and PNe in the LMC suggests that (a) SiC grains are formed more abundantly in the LMC than previous recognized (e.g., Zijlstra et al 2006); and (b) that the LMC metallicity allows SiC to form and survive in the late AGB phase and into the PN phase more efficiently than in the Galaxy.…”
Section: Spectral Featuresmentioning
confidence: 99%
“…Whereas SiC is commonly seen in C-star spectra, its occurrence in Galactic (Milky Way) planetary nebulae (PNe) is less common (Barlow 1983;Rinehart et al 2002;Casassus et al 2001), even though C-stars evolve into C-rich PNe. However, evolution of these grains from the C-star to PNe phase is not understood, and other spectral features (e.g., ∼ 11 − 12µm plateau due to PAH emission) may mask the SiC band (see Speck & Hofmeister 2004).…”
Section: Potential Uses Of New Data On N and K For Sic Over The Ir To Uvmentioning
confidence: 99%
“…Detection of an SiC feature near 11 µm provides a diagnostic for the nature of these objects. Furthermore, SiC is commonly found in extreme carbon stars and planetary nebulae (PNe) in the Large Magellanic Cloud (Stanghellini et al 2007;Bernard-Salas et al 2008;Gruendl et al 2008), and not commonly found in their Milky Way counterparts (Barlow 1983;Rinehart et al 2002;Casassus et al 2001;Speck et al 2009). Consequently SiC presents a tool for understanding the effect of metallicity on dust formation, evolution, and survival.…”
Section: Introductionmentioning
confidence: 99%